Conservative management for female urinary incontinence and pelvic organ prolapse review 2013: Summary of the 5th International Consultation on Incontinence. Issue 1 (15th November 2014) - Dumoulin, Chantale; Hunter, Kathleen F.; Moore, Katherine; Bradley, Catherine S.; Burgio, Kathryn L.; Hagen, S.; Imamura, M.; Thakar, R.; Williams, K.; Chambers, T.
Abstract : Aims: The objective of the 5th International Consultation on Incontinence (ICI) chapter on Adult Conservative Management was to review and summarize the new evidence on conservative management of urinary incontinence (UI) and pelvic organ prolapse (POP) in order to compile a current reference source for clinicians, health researchers, and service planners. In this paper, we present the review highlights and new evidence on female conservative management. Methods: Revision and updates of the 4th ICI Report using systematic review covering years 2008–2012. Results: Each section begins with a brief definition and description of the intervention followed by a summary, where possible, of both the state and level of evidence for prevention and treatment, and ends with a "grade of recommendation." The paper concludes with areas identified as requiring further research. Conclusions: For UI, there are no prevention trials on lifestyle interventions. There are, however, few new intervention trials of lifestyle interventions involving weight loss and fluid intake with improved levels of evidence and grade of recommendation. Outside of pre‐ and post‐natal pelvic floor muscle training (PFMT) trials for the prevention of female UI, there is a dearth of PFMT prevention trials for women with UI. PFMT remains the first‐line treatment for female UI with high levels of evidence and grades of recommendation. Bladder training levels of evidence and grades of recommendation are maintained. For POP, new evidence supports the effectiveness of physiotherapy in the treatment of POP and there are now improved levels of evidence and grades of recommendation. Neurourol. Urodynam. 35:15–20, 2016 . © 2014 Wiley Periodicals, Inc.